Teacher’s Compliment for Students and Its Impact on Their Interest in Learning English: A Case Study at the Second Grade of SMAN 7 Wajo - Nurul Aprianty; Baso Jabu; Geminastiti Sakkir (Journal of Excellence in English Language Education, 2026)
This study aims to find out how teachers give compliments to students when teaching English. This research used a qualitative descriptive method. The data collection in this study was carried out by observing the atmosphere in the classroom during the learning process and interviewing 6 students from SMAN 7 Wajo. The results of this study found that the teacher gives compliments to students verbally and non-verbally. For verbal compliment the teacher used words such as: "Good job", "Good", "Very good", "Good idea", "Amazing", and some advice for low grades, such as: "Don't give up easily", "Enthusiasm for learning". For non-verbal compliments, teachers used actions such as giving a thumbs up, nodding their heads, clapping their hands and giving appreciation to lower-grade students by gently touching their shoulders.